ESP NEEDS ANALYSIS OF PUBLIC ORDER POLICE OFFICERS - Ömer Gökhan Ulum (Informascope, 2017)
With this study, 105 public order police officers in the national police forces were surveyed in order to assess their needs when using English on the job. In other words, this study aimed at examining the needs, functions and problems of 105 police officers serving at the department of public order. The findings from the questionnaire with open ended questions displayed that, (1) speaking and listening are the most important skills, (2) four language skills are moderately difficult, (3) there are motivational factors important to learn English, and (4) the functional use of English is important for the public order police officers.  Recommendations and pedagogical implications were suggested.